High flying adored: How CEO narcissism influences firms' responses to above‐aspiration performance with risky organizational change - Kavuşan, Korcan; Mack, Daniel Z.; Mount, Matthew; Ertug, Gökhan (Strategic Management Journal, 2025)
Abstract Research Summary Research on performance feedback presents conflicting views on how above‐aspiration performance influences organizational change. Some studies argue that it constrains change due to a lack of organizational motivation, while others suggest that it enables change by expanding managerial discretion. Reconciling these perspectives, we suggest that managers’ narcissistic tendencies can fundamentally alter how a firm responds to above‐aspiration performance. We theorize and find evidence that high‐narcissism CEOs respond to above‐aspiration performance with more acquisitions—attention‐generating actions that align with their self‐enhancement motives, while under similar conditions low‐narcissism CEOs avoid acquisitions, due to their uncertainty and risk. Our findings highlight the interplay between managerial discretion and personal motivations in shaping strategic responses to performance feedback, offering new insights into the role of executive personality in corporate decision‐making. Managerial Summary Do successful firms pursue bold strategic moves—or play it safe when firm performance is strong? Our study seeks to answer this question and reconcile conflicting findings about how above‐aspiration performance influences managers’ decisions to undertake risky organizational change, such as corporate acquisitions. We show that it depends on CEO narcissism. High‐narcissism CEOs—who seek attention, hold an inflated self‐view, and are more egoistic—are motivated to initiate bold, high‐risk changes like acquisitions. In contrast, low‐narcissism CEOs—who avoid challenging tasks, hold a modest self‐view, and are sensitive to negative evaluation—are motivated to avoid bold, high‐risk changes like acquisitions. By showing how CEO narcissism affects firms’ risky change actions, we offer new insights into the role of executive personality in corporate decision‐making.